Effects of exposure to gadolinium on the development of geographically and phylogenetically distant sea urchins species. (July 2017) - Martino, Chiara; Bonaventura, Rosa; Byrne, Maria; Roccheri, Maria; Matranga, Valeria
Abstract: Gadolinium (Gd), a metal of the lanthanide series used as contrast agent for magnetic resonance imaging, is released into the aquatic environment. We investigated the effects of Gd on the development of four sea urchin species: two from Europe, Paracentrotus lividus and Arbacia lixula, and two from Australia, Heliocidaris tuberculata and Centrostephanus rodgersii . Exposure to Gd from fertilization resulted in inhibition or alteration of skeleton growth in the plutei. The similar morphological response to Gd in the four species indicates a similar mechanism underlying abnormal skeletogenesis. Sensitivity to Gd greatly varied, with the EC50 ranging from 56 nM to 132 μM across the four species. These different sensitivities highlight the importance of testing toxicity in several species for risk assessment. The strong negative effects of Gd on calcification in plutei, together with the plethora of marine species that have calcifying larvae, indicates that Gd pollution is urgent issue that needs to be addressed. Highlights: Gadolinium has severe effects on sea urchin embryos development. We compared the effects on geographically and phylogenetically distant species. Gd causes dose-dependent skeleton damage, no effect on other embryonic territories. Different species have different sensitivities to Gd. To assess the hazard, toxicity tests should be carried out on more than one species.